Evaluation of the anti-inflammatory and cytotoxic properties of the methanolic fruit extract of Batuan, Garcinia binucao (Blanco) choisy - Creer, Leander C. (2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) are associated with several adverse side effects; thus, there is a need to find alternative approaches that can serve as safe and affordable anti-inflammation medications. This study evaluated the anti-inflammatory property of the Garcinia binucao methanolic fruit extract using albumin protein denaturation and cytotoxic activity using brine shrimp lethality assay. The total phenolic content obtained using the Folin-Ciocalteu assay and the total flavonoid content obtained using the aluminum chloride colorimetric method of the extract were 60.62+/- 1.45 mg GAE/g dry extract or equivalent to 0.77 mg QE/100 g fresh weight sample, respectively. Results show that the extract has a moderate anti-inflammatory activity at 5 mg/mL with 46.54% and it also exhibited a cytotoxic effect on brine shrimp at 0.0897 mg/mL after 24 hours. Thus, the G. binucao methanolic fruit extract can be a potential anti-anflammatory and cytotoxic agent which can be further explored in the future.